Legal Protection of Girls Victims of Sexual Violence - Noviyanti Noviyanti; Rizanizarli Rizanizarli; Sri Walny Rahayu (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Article 76D of Law Number 35 of 2014 explicitly prohibits all forms of sexual violence against children, a prohibition further reinforced through Law Number 12 of 2022 on the Crime of Sexual Violence; yet incidents of child sexual violence continue to be recorded annually, underscoring a persistent gap between normative prohibition and practical reality. Employing an empirical juridical methodology through structured interviews and comprehensive literature reviews, this study examines the institutional roles of the Women and Children Service Unit of the Resort Police, the Women's Empowerment, Child Protection and Family Planning Office, and the Social Service Agency in safeguarding the rights of female child victims in Bener Meriah Regency, while identifying impediments to effective legal protection and investigating victims' pathways to justice. Findings reveal that although legal protection has been pursued through both preventive and repressive measures, implementation remains constrained by regulatory obstacles, limited institutional capacity, deficient public legal awareness, entrenched victim-blaming attitudes, and shame-oriented cultural norms channeling disputes toward customary resolution mechanisms collectively resulting in the suboptimal actualization of victims' rights to restitution, state compensation, and psychological rehabilitation. Accordingly, the study recommends the formulation of integrated regulatory frameworks and standardized operating procedures, reinforcement of inter-agency coordination, and cross-sectoral synergy directed at dismantling informal settlement practices and reducing societal stigmatization of sexual violence survivors.